Interconnecting Musicologies: Decoding Mahler's Sixth Symphony - Niall O'Loughlin (Muzikološki Zbornik, 2003)
This paper aims to establish a possible model for a multi-dimensional approach to understanding a complex musical work, using a number of interconnecting musicologies. In the 19th century the symphony was often considered an abstract musical creation, but in other cases a programmatic work. The first four symphonies of Gustav Mahler are programmatic in that three set words to music, while extra-musical interpretations can easily be inferred for all four. The next three symphonies can be variously understood as abstract symphonies because they adhere to a pattern of four or five movements of contrasting character without any explicit programme. By using the musicology of traditional formal methods one can analyse and thus understand the workings of themes and motives and of the structures of sonata form, rondo and scherzo, but this seems in the studies of some commentators to have only limited application. All three have features which suggest programmatic elements, even the most 'classical' of the three, the Sixth Symphony. Investigations of the musicology of the musical imagery of this work, e.g. the Fate motive, the hammer blows in the finale, the 'pastoral' episodes, and the use of cowbells, indicate that there are other forces at work in the symphony. To uncover the implications of these we must look in other directions, to other musicologies. The next is biographical and points to some difficulty on the part of the composer to establish the order of the two middle movements, something which has a strong bearing on the overall meaning of the work. While the scherzo preceded the Andante in the score published before the premiere, Mahler reversed the order for all performances that he conducted and for the revised score. This order was reversed again by Erwin Ratz for the collected edition on some very slender evidence and some which is now discredited. Musical arguments have continued but the biographical evidence is so strong that Ratz's views are substantially if not totally undermined. Tonal evidence reinforces this position, making it possible now to understand Mahler's plan in an unambiguous way. At this point we can introduce the musicology of narrative. With the musicologies of traditional analysis, of imagery, of biography, and of tonality revealed, one can now proceed to investigate the progress of the work from beginning to end. In this way all the elements come into proper perspective with an overall plan suggesting a positive interpretation of the first two movements, with an idyllic situation at the end of the slow movement, and a pessimistic outcome of the combination of a sinister scherzo and overwhelming finale. In conclusion it is a mistake to think that each of these musicologies presented here as mutually exclusive and of no significance to another. In order to derive the most from a multi-faceted work such as Mahler's Sixth Symphony, it is essential to take account of all these procedures, not singly but fused together as a co-ordinated unit.